2017
DOI: 10.1111/ijlh.12749
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of the microINR® point‐of‐care INR‐testing system

Abstract: The microINR instrument is accurate and precise for monitoring warfarin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…In this study, high levels of dosage concordance were observed (85.46%). This concurs with the results of Lawrie et al and Joubert et al on the CoaguChek XS Plus and the microINR ® , respectively . Although, the mean laboratory INR was significantly higher than the qLabs POC device ® INR ( P < .0001); the clinical agreement was >90% for INR values within ±0.5 units or ±30% for INR ranges below and within the INR target range, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, high levels of dosage concordance were observed (85.46%). This concurs with the results of Lawrie et al and Joubert et al on the CoaguChek XS Plus and the microINR ® , respectively . Although, the mean laboratory INR was significantly higher than the qLabs POC device ® INR ( P < .0001); the clinical agreement was >90% for INR values within ±0.5 units or ±30% for INR ranges below and within the INR target range, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The qLabs POC device ® was found to be reliable and robust with an error message rate of <5%. This compares favorably with the safety and reliability of other available POC devices, such as the SmartCheck INR ® , the CoaguChek XS Plus ® , and the micro- 15,24,25 In this study, the most frequent error observed was the operator-dependant message of "insufficient blood added to the sample well" (n = 7, 2.67%). This highlights the importance of initial training.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Before affordable generic NOACs become available, warfarin will remain the anticoagulant of choice for the management of AF in SSA . To reduce the financial and human resources required for conventional INR monitoring, point‐of‐care INR testing has been proposed and its validity has been demonstrated in some studies in SSA …”
Section: Discussionmentioning
confidence: 99%